POTENSI SUMBER DAYA LOKAL PANTAI KAMPUNG PELANGI SEBAGAI UPAYA PENGEMBANGAN DESA WISATA DI RANDUPUTIH KECAMATAN DRINGU PROBOLINGGO - Husni Mubaroq,; Murtias Puji Astutik, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Various efforts from various parties, especially the government, are trying to reduce poverty to the maximum. The tourism village program is a reference for community empowerment by developing in an area to cultivate the potential of local resources as an effort to overcome poverty in an area. This research method as outlined is a qualitative descriptive research method. The focus of this research is the government and the village community in an effort to empower the community to improve welfare in Randuputih Village, Dringu District, Probolinggo Regency. Therefore, this study will discuss the tourism village program as a manifestation of community empowerment in empowering the community in Randuputih Village. This research is important because it will analyze the form of community empowerment through Tourism Villages in Randuputih Village. This study will provide insight in the context of developing Tourism Villages so that people can take advantage of the local potential that exists in the Tourism Village.